A Biostimulant Seed Treatment Improved Heat Stress Tolerance During Cucumber Seed Germination by Acting on the Antioxidant System and Glyoxylate Cycle - Campobenedetto, Cristina; Grange, Eric; Mannino, Giuseppe; van Arkel, Jeroen; Beekwilder, Jules; Karlova, Rumyana; Garabello, Christian; Contartese, Valeria; Bertea, Cinzia M. (Frontiers in Plant Science, 2020)
Seed enhancement technologies have the potential to improve germination and seedling growth under environmental stress. The effects of KIEM®, an innovative biostimulant based on lignin derivatives and containing plant-derived amino acids and molybdenum, were investigated on cucumber (Cucumis sativus L.) seed germination. To determine the metabolic targets of this product, biometric, transcriptional and biochemical analyses were carried out on both nontreated and KIEM®-treated seeds incubated for 24 and 48 h under standard (28°C) and heat stress (35°C) conditions. The application of the biostimulant as a seed treatments increased the percent germination (+6.54%) and fresh biomass (+13%) at 48 hours, and decreased the content of H2O2 in treated seeds at 28°C (-70%) and at 35°C (-80%). These changes in biometric and biochemical properties were accompanied by changes in expression levels of the genes coding for ROS-producing (RBOH) and scavenging (SOD, CAT, GST) enzymes and their specific activity. In general, the treatment with KIEM® in heat-stress condition appeared to stimulate a higher accumulation of three scavenger gene transcripts: CuZnSOD (+1.78), MnSOD (+1.75), and CAT (+3.39), while the FeSOD isoform was dramatically downregulated (0.24). Moreover, the amount of non-protein thiols, important antioxidant molecules, was increased by the biostimulant after 48 hours (+20%). Taken together these results suggest that KIEM® acts through mitigation of the effects of the oxidative stress. Moreover, after 48 hours, the pre-sowing treatment with KIEM® increased the transcription levels (+1.5) and the activity of isocitrate lyase (+37%), a key enzyme of the glyoxylate cycle, suggesting a potential effect of this product in speeding up the germination process. Finally, the chemical characterization of KIEM® identified five essential and three non-essential amino acids, and others bioactive compounds, including five organic and inorganic acids that might be potentially involved in its activity. Based on these data, insights on the potential mechanism of action of the biostimulant, suggested that there are broader applications as a product able to increase seed tolerance to different abiotic stress typical of adverse environmental conditions.